M7G-related LncRNAs: A comprehensive analysis of the prognosis and immunity in glioma - Wu, Shuaishuai; Ballah, Augustine K.; Che, Wenqiang; Wang, Xiangyu (Frontiers in Genetics, 2022)
Today, numerous international researchers have demonstrated that N7-methylguanosine (m7G) related long non-coding RNAs (m7G-related lncRNAs) are closely linked to the happenings and developments of various human beings' cancers. However, the connection between m7G-related lncRNAs and glioma prognosis has not been investigated. We did this study to look for new potential biomarkers and construct an m7G-related lncRNA prognostic signature for glioma. First, we identified 658 m7G-related lncRNAs using the " limma " package. Then, eight lncRNAs associated with prognosis were obtained and used to construct the m7G risk score model by lasso and Cox regression analysis methods.And we used Kaplan-Meier analysis, time-dependent ROC, principal component analysis, clinical variables, independent prognostic analysis, nomograms, calibration curves, and expression levels of lncRNAs to determine the accuracy of the model. Importantly, we validated the model with external and internal validation methods and found it has strong predictive power.Finally, we performed functional enrichment analysis (GSEA, aaGSEA enrichment analyses) and analyzed immune checkpoints, associated pathways, and drug sensitivity based on predictors. In conclusion, we successfully constructed the formula of m7G-related lncRNAs with powerful predictive functions. Our study provides some instructional value for the analysis of glioma pathogenesis and offers potential research targets for glioma treatment and scientific research.